Estabelecimento do meio de cultura e conservação da viabilidade polínica de hemerocale - Eberling, Tatiane (2019)
The hemerocale is a monoic plant used in inter and intraspecific hybridizations, which has given rise to a great diversity of cultivars with different colors and forms through programs of improvement. Taking the aforementioned into account, the objective of this work was to establish a culture medium to evaluate pollen viability in day-old cultivars and to evaluate the dehydration and storage conditions of pollen grains regarding their germination and viability. A sequential experiment was carried out in the laboratory, where the cultivar Morgana AS Piske was used for the establishment of the culture medium, in which the pH ranges (4, 5, 6, 7) together with concentrations of agar (4, 6, 8, 10 g L-1). In the following test, concentrations of sucrose (0, 30, 60, 90, 120 g L-1) were tested. Afterwards, concentrations of boric acid (0, 400, 800, 1200 mg L-1) were added to the medium and, finally, calcium nitrate concentrations (0, 200, 400 and 800 mg L-1). After the establishment of the culture medium, the incubation time required for maximum germination of the pollen grains was evaluated. The obtained medium was tested in four cultivars, aiming at the verification of germination percentages. For the second part of the experiments, four times (0, 12, 24, 48 hours) and two drying sites (BOD greenhouse at 25ºC and silica gel desiccator) were evaluated. In vitro germination and pollen viability tests were performed. After the determination of the best time and place of drying, the pollen grains were stored. They were stored in a freezer at -20 ± 3ºC, refrigerator at 4 ± 3ºC and BOD 25ºC, for 0, 7, 14, 21 and 28 days. After storage, germination and viability tests were repeated. The highest percentage of in vitro germination occurred with the concentrations of 4 g L-1 agar, 74.6 g L-1 sucrose, 800 mg L-1 boric acid, 590 mg L-1 calcium nitrate, pH of 5.74 and ideal incubation time of 3 hours, being cv. Regina the one with the highest percentage of germination. The pollen grains of the hemerocale cultivars had a higher percentage of germination when fresh, and there was no need for dehydration. The best storage site was the freezer, where the pollen kept 50% of its germination, even after 28 days of storage. The 1% dye 2,3,5-triphenyltetrazolium (TTC) was not efficient in determining the pollen viability of hemerocale pollen.